Role of Emotional Intelligence in Career Advancement of University Teachers - Fida, Farah; Akhter, Nasreen; Iqbal, Sabiha; Noor, Aks E; Salamat, Lubna (2021)
Purpose of the study: This paper aimed to discuss the theories of emotional intelligence and its role in career advancement in the institutions of working in the field of higher education.